THE RELATIONSHIP BETWEEN THE NUTRITIONAL STATUS OF POSTPARTUM WOMEN AND THE WOUND HEALING PROCESS POST SECTIO CAESAREA AT TANJUNG PURA HOSPITAL IN 2024 - Dyanti SR Butar-Butar; Bakara, Sri Muliana Putri; Hutabarat, Dewi Sartika; Dinata, Daniel Permanda; Sitompul, Julita Sari; Manurung, Revalina (Yayasan Nuraini Ibrahim Mandiri, 2024)
Background: Sectio caesarea (SC) is a delivery procedure that can cause complications, including prolonged wound healing. The nutritional status of postpartum women plays an important role in accelerating the postoperative wound healing process. Malnutrition can slow tissue regeneration, increase the risk of infection, and prolong the recovery period.Objectives: This study aims to analyse the relationship between the nutritional status of postpartum women with the post SC wound healing process at Tanjung Pura Langkat Hospital in 2023.Methods: This study used an analytical survey design with a cross-sectional approach. The sample consisted of 30 postpartum mothers who were selected using purposive sampling technique. Nutritional status was measured by upper arm circumference (LILA), and wound healing was assessed using the REEDA scale. Data analysis used chi-square test with a significance level of 0.05.Results: Of the 30 respondents, 66.6% had normal nutritional status, while 33.3% had chronic energy deficiency (CED). Wound healing was faster in mothers with normal nutritional status (100%) compared to mothers with SEZ (0%). The chi-square test showed a significant relationship between nutritional status and post SC wound healing (p=0.000).Conclusion: Good nutritional status is associated with faster wound healing in post SC mothers. Therefore, the fulfilment of optimal nutrition is very important for postpartum women to accelerate the postoperative recovery process.